PELATIHAN ICE BREAKING PADA GURU SD TUNAS PELITA BINJAI UNTUK PENINGKATAN HASIL BELAJAR SISWA - Erilia, Risky (LPPM STKIP AL MAKSUM, 2025)
ABSTRACT Ice breaking training for teachers plays a crucial role in improving the quality of learning in elementary schools. The objective of this activity was to equip teachers at Tunas Pelita Elementary School with the skills to implement effective ice-breaking to create a pleasant learning atmosphere and encourage active student participation. The activity was held on Thursday, Nov 13, 2025, with 20 teachers participating. The implementation method included interactive lectures, group discussions, and simulations of ice-breaking practices in classroom situations. The training was divided into three stages: preparation, implementation, and evaluation. The results of the activity showed that teachers became more confident and creative in managing the classroom, and were able to create a conducive atmosphere from the beginning of the lesson. Evaluation through a questionnaire showed an increase in participants' understanding of the concept and techniques of ice-breaking. Thus, this training made a real contribution to improving student learning outcomes by increasing their motivation and engagement in class.